Effectiveness of Aluminium Electrode-Based Electrocoagulation in Monopolar Configuration in Removing Suspended Solids and Turbidity from Car Wash Wastewater - Muhammad Harith Yasin; Ab. Aziz, Nur Adila (Journal of Advancement in Environmental Solution and Resource Recovery, 2026)
The increasing demand for car wash services in Malaysia has led to the release of untreated car wash wastewater into water bodies, negatively impacting the environment and aquatic life. The primary goal of this research is to optimise the operational parameters of electrocoagulation for removing suspended solids, colour, and turbidity from car wash wastewater. Additionally, this study also analyses the sludge volume index (SVI) at the end of each treatment cycle. It assesses the occurrence of the passivation effect during electrocoagulation by weighing the electrodes after every cycle. This research identifies the optimal parameters for efficiently removing total suspended solids (TSS), turbidity, and colour from car wash wastewater. The electrocoagulation (EC) process was carried out using aluminium electrodes, with current density levels ranging from 20 to 100 A/m², initial pH values between 6 and 11, and contact times varying from 30 to 180 minutes while assessing the pollutants’ removal efficiency. The distance between the electrodes and the settling time was consistently maintained at 5 centimetres and 30 minutes, respectively. The optimal operating parameters identified included a current density of 45 A/m², an initial pH of 7, and a contact time of 140 minutes. Under these specified conditions, the removal efficiencies achieved were 92.09% for turbidity, 92.70% for colour, and 96.34% for suspended solids. The study also assessed the sludge volume index (SVI), which indicated poor sludge settleability (295.05 mL/g), and the electrode passivation effects, where a hydroxide layer formation reduced long-term electrode effectiveness. The electrocoagulation process has significant potential for removing physical contaminants from car wash wastewater, particularly turbidity, suspended solids, and colour. Future efforts to enhance removal efficiency could include minimising the spacing between electrodes and increasing their total working surface area.